DIFFERENCES IN PARENTING PATTERNS BETWEEN GENERATIONS X, Y, Z AND ALFA - Maribeth, Annisa Lidra; Hamda, Rialta; Widia Sari; Maidarmi Handayani; Ghaniyyatul Khudri; Ramadhani VN; Salsabila R (Journal of Public Health Science, 2024)
Parenting styles or other caregivers can have an impact on children's mental health. Every family uses a different approach to parenting, typically carried over from their previous parents, when it comes to raising children. Every parent undoubtedly hails from a diverse range of backgrounds and generations. To maximize children's mental health, it is therefore essential to understand how parenting styles are passed down through generations in order to give suitable interventions. Generations X born between 1965-1980 ; Generation Y or Millennials were born between 1980-1996; Generation Z was born in 1997-2010 and Alpha generation, born in 2010-2025. Finding out how parents apply different parenting philosophies to kids from generations X, Y, Z, and Alpha is the goal of this literature. The systematic review approach is used in this literature. The PRISMA-P protocol (Preferred Reporting Items for Systematic Review and Meta-Analysis protocol) was the methodology employed in 2020. Research was gathered by looking via Google Scholar for the original source data. PICOS (Population Intervention Compare Outcome-Study Design) keyword search method. Out of the 60 studies that were located, eight were used in this analysis. The findings of this literature review highlight the disparities in parenting styles among the generations. Parents of generations X, Y, and Alpha generally apply a democratic parenting approach, which is sometimes referred to as drone parenting. Meanwhile, the application of parenting patterns for generation Z children shows quite large variations. Parents from this generation apply authoritarian, overprotective, permissive, self-disclosure, and narcissistic parenting patterns and give excessive appreciation or praise to children, which has created what is known as the "Strawberry Generation," meaning generation Z children tend to be more vulnerable.